A Study on Marginal Continuty of Shoulder and Chamfer Finish Line of Metal Crown - Mahenaz Munira; Faruk Nahar; Nasima Khatun; Mahamuda Khatun; Alia Sultana (Update Dental College, 2017)
Background: Marginal continuty is very important for the longevity of restoration .The junction between the cemented restoration and the tooth is always a potential site for recurrent caries, gingivitis and periodontitis and ultimately failure of crown as well as teeth. Hypothesis: Marginal continuity for shoulder finish line for anterior teeth and chamfer for posterior teeth are equally effective. Objectives: To evaluate the marginal continuity of metal crown. Methods: Thirty extracted human teeth were prepared with shoulder margin (group-A) and another thirty teeth were prepared with chamfer (group-B) as methodically. Metal crown was fabricated by lost wax technique of casting procedure. All of the crowns (both group-A and group-B) were cemented by glass inomer luting cement. Each crown was sectioned in faciolingual direction at the midpoint of each surface by slow speed isomet saw. The sectioned crowns were examined under sreriomicroscope for measurement of marginal continuty. Data were collected on the basis of marginal continuty of each crown was compared. Collected data were processed and analyzed using SPSS (Statistical Package for Social Service) version 12. Results: The frequency distribution of marginal continuity were statistically non significant between two groups. Conclusion: All metal crowns had greater continued margin than discontinued margin. Update Dent. Coll. j: 2017; 7 (1): 26-29